2009
DOI: 10.1007/s00264-009-0859-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Achilles tendon rupture reconstruction using a modified flexor hallucis longus transfer

Abstract: The purpose of this study was to report the management and outcome of 11 patients presenting with chronic Achilles tendon (AT) rupture treated by a modified flexor hallucis longus (FHL) transfer. Seven patients presented with a neglected AT rupture, one with a chronic AT rupture associated with Achilles tendinosis and three with an AT re-rupture. AT defect after fibrosis debridement averaged 7.4 cm. In addition to FHL transfer, we performed an augmentation using the two remaining fibrous scar stumps of the rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
110
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 27 publications
5
110
0
Order By: Relevance
“…Previous studies have shown comparable results [4][5][6][7][8][9][13][14][15][16]. In the study of Wegrzyn et al [8] the postoperative deficit in plantar flexion torque averaged 28%, and 41% in the study of Wapner et al [4].…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Previous studies have shown comparable results [4][5][6][7][8][9][13][14][15][16]. In the study of Wegrzyn et al [8] the postoperative deficit in plantar flexion torque averaged 28%, and 41% in the study of Wapner et al [4].…”
Section: Discussionsupporting
confidence: 67%
“…This study also showed that FHLT transfer using a technique with a single incision and tendon fixation with a bone anchor, provided comparable results to those patient series where two incision technique or tendon fixation through a calcaneal bone tunnel were used [5,6,8]. A single incision technique with a fixation bone anchor or interference screw can be performed from relatively short skin incision and without exposure of the calcaneus for preparing the bone tunnel.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations